Influence of the weeds management on the mite diversity in organic coffee crop - Neto, Marçal Pedro; Reis, Paulo Rebelles; Silva, Rogério Antônio; Zacarias, Mauricio Sergio (Coffee Science - ISSN 1984-3909, 2015)
The control of pests, diseases and weeds become an obstacle to food production in an organic system. Studies demonstrate that the management of weeds in coffee decreases the number of insects with the potential to become pests and provides increased natural enemies, and consequently keeps the pests at low levels, without causing damage. Of pest mites, Oligonychus ilicis (McGregor), Brevipalpus phoenicis (Geijskes) and Polyphagotarsonemus latus (Banks) are those that can cause significant losses to coffee production. Aimed to evaluate the effect of management of adventitious plants in diversity of mites in coffee (Coffea arabica L.) grown organically. The experiment consisted of five treatments and five repetitions in a randomized block design. On the experiment was accomplished four types of management of weeds between the lines, total mowing, mowing alternating between the lines, total manual weeding, hand weeding alternating between the lines and control (treatment without management). During 24 months were collected 25 coffee leaves on each replicate, packed in plastic bags and taken to the laboratory for extraction of dust mites by washing method. The resulting material was analyzed with a stereoscopic microscope and mites found were fixed on slides for identification, where possible, to the species level. Therefore, in general, the type weeds management positively influenced the number of predatory mite Euseius citrifolius Denmark and Muma. For predators Euseius concordis (Chant) and Neoseiulus benjamini (Schica), the absence of management of weeds was beneficial. The largest number of pest mites was observed on treatment with low diversity of weeds.